2015
DOI: 10.1155/2015/290861
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation, Heritability, and Diversity Analysis of Upland Rice (Oryza sativaL.) Genotypes Based on Quantitative Traits

Abstract: Upland rice is important for sustainable crop production to meet future food demands. The expansion in area of irrigated rice faces limitations due to water scarcity resulting from climate change. Therefore, this research aimed to identify potential genotypes and suitable traits of upland rice germplasm for breeding programmes. Forty-three genotypes were evaluated in a randomised complete block design with three replications. All genotypes exhibited a wide and significant variation for 22 traits. The highest p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 13 publications
14
44
0
Order By: Relevance
“…Similar results were reported by Dutta et al, (2013);Singh et al, (2014) and Tuhina-Khatun et al, (2015) in rice. It is interesting to note that this difference was low for all the characters except panicle weight and stem weight, indicating that these characters were less influenced by environment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were reported by Dutta et al, (2013);Singh et al, (2014) and Tuhina-Khatun et al, (2015) in rice. It is interesting to note that this difference was low for all the characters except panicle weight and stem weight, indicating that these characters were less influenced by environment.…”
Section: Discussionsupporting
confidence: 91%
“…In order to assess and quantify the genetic variability among the genotypes for the characters under study the variance components and values of heritability and genetic advance were estimated following the formula given by Burton and De Vane (1953);and Johnson et al (1955) and applied by Tuhina-Khatun et al (2015). Phenotypic and genotypic variances were estimated using the following formula: Both genotypic and phenotypic coefficients of variability were estimated using the formula below:…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were reported by (Dutta et al, 2013;Singh et al, 2014;Tuhina-Khatun et al, 2015) in rice. The trait like yield panicle -1 which show higher difference between PCV and GCV indicated that environmental effect on the expression of those traits is higher.…”
Section: Estimate Of Genetic Parameterssupporting
confidence: 90%
“…The exception was cycle 4 for GY, in which  h p 2 did not differ statistically from zero (α=0.05) due to the strong effect of residual variance (  σ 2 ) (Tables 2 and 3). The magnitude of the  h p 2 obtained in the present study for both traits (Table 3) is similar to those found in other works with upland rice crops (Colombari Filho et al, 2013;Ahmad et al, 2015;Tuhina-Khatun et al, 2015).…”
Section: Resultssupporting
confidence: 92%
“…Although several works have estimated the genetic parameters of autogamous species, such as rice (Bueno et al, 2012;Colombari Filho et al, 2013;Ahmad et al, 2015;Tuhina-Khatun et al, 2015), Falconer & Machay (1996) pointed out that the obtained results are only valid for the material of the researched population and for the environmental conditions in which the study was carried out. For this reason, the continuous study of the estimates of the variance components of a population is essential to guide genetic breeding in recurrent selection, in which the magnitude of genetic variability during the selection cycles may be affected by several different factors, such as, for example, the size of the sample for recombination, which, in turn, depends on the effective size of the recombination unit (Bernardo, 2010).…”
Section: Introductionmentioning
confidence: 99%